A Memorial to Those Who Fought in the War Everyone Wants to Forget - David H. Bell (Oz, 1982)
Sigmund Freud once compared the mind and psyche of man to the city of Rome. Just as Rome developed by building upon, modifying, submerging, and eliminating gradually through time architectural and urban fragments, so does memory work by a sedimentation of experience to create a self for each person...